2018
DOI: 10.1177/0194599818765718
|View full text |Cite
|
Sign up to set email alerts
|

Role of Psychosocial Factors on Communicative Participation among Survivors of Head and Neck Cancer

Abstract: Objective The purpose of this study was to examine the unique contribution of psychosocial factors, including perceived social support, depression, and resilience to communicative participation, among adult survivors of head and neck cancer (HNC). Study Design Cross-sectional. Setting University-based laboratory and speech clinic. Subjects and Methods Adult survivors of HNC who were at least 2 years posttreatment for HNC completed patient-reported outcome measures, including those related to communicative part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
3
10
0
3
Order By: Relevance
“…Other self-reported variables including cognitive symptoms, depression, perceived social support, and resilience are also significantly associated with communicative participation. 73,77,78 These findings support the premise that communicative participation is affected by multiple non-speech impairments as well as environmental and personal factors in HNCA survivors, as well as in other populations.…”
Section: Head and Neck Cancersupporting
confidence: 71%
“…Other self-reported variables including cognitive symptoms, depression, perceived social support, and resilience are also significantly associated with communicative participation. 73,77,78 These findings support the premise that communicative participation is affected by multiple non-speech impairments as well as environmental and personal factors in HNCA survivors, as well as in other populations.…”
Section: Head and Neck Cancersupporting
confidence: 71%
“…The CPIB measures the impact of HNC on communication in everyday settings, or “communicative participation.” Items in the CPIB were developed on the basis of a literature review 8 and qualitative studies 13 , 14 . The CPIB was subsequently validated in several large‐scale psychometric studies across a number of clinical populations, including HNC, 12,15,16 and has been used to investigate relationships between communicative participation and other HNC outcomes such as speech intelligibility 17 and depression 18 , 19 . One advantage of the CPIB is that it is able to capture communication difficulties, regardless of whether deficits are related to speech, voice, or other contributing factors.…”
mentioning
confidence: 99%
“…The effect of cancer location on social participation gained attention in recent researches; however, the relationship could not be made. 29,30 Our study showed that HNC survivors' social participation decreased in the order of oral cavity cancer, pharyngeal cancer (β = 3.4 ± 1.39), and laryngeal cancer (β = 9.2 ± 3.80) after considering all variables. A possible explanation for the poor social participation in laryngeal cancer with swallowing impairment could also be associated with the laryngectomy 31,32 and the use of a voice prosthesis.…”
Section: Discussionmentioning
confidence: 72%